A dictionary of weights, measures, and units - Fenna, Donald, 1932- (Oxford University Press, 2002)
Searchable database with over 1,500 entries providing clear definitions of all the units, prefixes, and styling of the Systáeme International (SI), as well as industry-specific and traditional terms currently in use.
Keywords: Weights and measures -- Dictionaries.; Measurement -- Dictionaries.; Units of measurement -- Dictionaries.; elektronické knihy; electronic books